The rights of same-sex partners in the European Union and Serbia in the field of marriage law - Samardžić, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
This paper tries to present the historical path that some European countries have crossed in the area of ​​same-sex partners, but also to present the way in which the attitude of the European Court of Human Rights has moved on this issue, as a possible models which may be placed before the Serbia as requirements in the future. Also, it is given the review of the legislation of certain countries of the European Union and posed a question whether the proposed solutions are acceptable and whether it can lead toharmful consequences about which proponents of same-sex marriages are not thinking now.